Association between adverse oral conditions and cognitive impairment: A literature review - Wei, Tianhao; Du, Yifeng; Hou, Tingting; Zhai, Chunjuan; Li, Yuqi; Xiao, Wei; Liu, Keke (Frontiers in Public Health, 2023)
Oral environment deterioration results from a lack of self-cleaning ability in patients with cognitive dysfunction but is also a risk factor for cognitive dysfunction. Adverse oral conditions can be alleviated and improved through a self-management and medical examination. In this review, the epidemiological evidence of previous studies is integrated to highlight the relationship between periodontitis, tooth loss, oral flora, oral dysfunction and cognitive dysfunction, emphasizing the importance of oral health for cognition. The results show that poor oral condition is associated with cognitive impairment. Although many previous studies have been conducted, there is a lack of higher-level research evidence, different judgment criteria, and conflicting research results. There is a bidirectional relationship between oral health and cognitive dysfunction. A comprehensive analysis of the relationship between oral health and cognitive dysfunction that explores the relationship and takes measures to prevent cognitive dysfunction and control the progression of such diseases is warranted in the future.